ORGANIC MATTER AND NUTRIENT PROFILE OF THE TWO-CURRENT-REGULATED-ZONE IN THE SOUTHWESTERN SUMATRAN WATERS (SSW) - Wahyudi, Aan Johan; Iskandar, Mochamad R.; Meirinawati, Hanny; Afdal, .; Vimono, Indra B.; Afianti, Nur F.; Sianturi, Oksto R.; Wirawati, Ismiliana; Darmayati, Yeti; Helfinalis, .; Sidabutar, Tumpak (Marine Research in Indonesia, 2017)
The Indian Ocean is influenced by monsoon systems which alter the oceanâs physical and chemical properties. Specifically, the southwestern Sumatran waters in the eastern Indian Ocean are considered a dual current regulated zone i.e. affected by South Equatorial Counter Current (SECC) and South Java Current (SJC). This area is considered as having an important role in the transfer of organic matter or the biological pump. However, the information about this area is minimal, especially in terms of organic matter and nutrient profile. This study will update the recent information about the area, including the profile of particulate organic matter (POM), macro-nutrients, total suspended solids (TSS), macromolecule-degradingbacteria, and soft bottom macrobenthic organisms sampled from 26 stations in both the SECC-regulated zone and the SJC-regulated zone. The physical profile is typical of tropical watersand both zones have a distinct profile of organic matter and nutrients. The particulate organic carbon (POC), particulate organic nitrogen (PON), and TSS of the SECC-regulated zone can be considered higher than those of the SJC-regulated zone. This region is categorized as mesotrophic waters, especially from the surface up to 100 m. The production of nutrients and organic matter in the water column in this area contribute significantly to the abundance of heterotrophic bacteria and benthic organisms.